Tree species influence on street microclimatic conditions - Tan, Xiu Han (2019)
Urbanization and urban heat island (UHI) have become more intense and caused many heat-related diseases to urban population. Trees serve as an asset to improve urban street microclimate conditions. However, physical tree characteristics such as canopy shape, size, leaves, branching characteristics and arrangement varies among different tree species, thus may influence the street microclimate. Therefore, the objectives of this study were to evaluate microclimate benefits of urban street trees and effects of different trees with different leaf and canopy characteristics on street microclimatic conditions. Five different tree species with different canopy and leaf characteristics were studied in early 2019. Microclimatic measurements such as air temperature, solar radiation, wind speed, and relative humidity were measured on pedestrian walkways below tree canopies and in open areas during solar noon time, 12pm – 2 pm on seven hot and sunny days. Trees with different Plant Area Index (PAI) were determined using digital photography. Street with trees provided significantly greater microclimatic benefits compared to the open area and microclimate benefits were greater with increasing tree PAI index. Samanea saman showed the greatest microclimate benefits by greatest reduction in air temperature by 1.4⁰C and had the highest relative humidity with 53.7% while Roystonea regia provided the least microclimate benefits as it had the highest rate of air temperature with 35.1 ⁰C, solar radiation with 501.6 W/m2. However, there were no significant differences of different five tree species on wind speed measurement. Present study indicated that different tree species with different physical characteristics such as canopy density and shape, tree height, branching and leaves arrangement affects the street microclimatic conditions. This study assists urban planners in proper selection of street tree species according to their improvement of microclimatic conditions.